Analysis of FUS, PFN2, TDP-43, and PLS3 as potential disease severity modifiers in spinal muscular atrophy - Wadman, Renske I. (Neurol Genet, 2019)
OBJECTIVE: To investigate mutations in genes that are potential modifiers of spinal muscular atrophy (SMA) severity. METHODS: We performed a hypothesis-based search into the presence of variants in fused in sarcoma (FUS), transactive response DNA-binding protein 43 (TDP-43), plastin 3 (PLS3), and profilin 2 (PFN2) in a cohort of 153 patients with SMA types 1–4, including 19 families. Variants were detected with targeted next-generation sequencing and confirmed with Sanger sequencing. Functional effects of the identified variants were analyzed in silico and for PLS3, by analyzing expression levels in peripheral blood. RESULTS: We identified 2 exonic variants in FUS exons 5 and 6 (p.R216C and p.S135N) in 2 unrelated patients, but clinical effects were not evident. We identified 8 intronic variants in PLS3 in 33 patients. Five PLS3 variants (c.1511+82T>C; c.748+130 G>A; c.367+182C>T; c.891-25T>C (rs145269469); c.1355+17A>G (rs150802596)) potentially alter exonic splice silencer or exonic splice enhancer sites. The variant c.367+182C>T, but not RNA expression levels, corresponded with a more severe phenotype in 1 family. However, this variant or level of PLS3 expression did not consistently correspond with a milder or more severe phenotype in other families or the overall cohort. We found 3 heterozygous, intronic variants in PFN2 and TDP-43 with no correlation with clinical phenotype or effects on splicing. CONCLUSIONS: PLS3 and FUS sequence variants do not modify SMA severity at the population level. Specific variants in individual patients or families do not consistently correlate with disease severity.